Food, books, cities - Burgio, Gianluca (E|C, 2020)
This text is inspired by two considerations: the first is the intimate bond between food and the city; the second relates to the fact that there is almost no architectural literature dealing with food. This work - which was born as part of a project of the Habitar Research Group of the Universitat Politècnica de Catalunya - has highlighted the fact that food and the city are intimately related and that the food / architecture combination can be found in an extensive bibliography, often found outside the architectural sphere, made up of materials and documents which, from the disciplinary point of view (of architecture), appear very distant and yet full of ideas and intuitions who manage to narratively define how food can shape space. As a result, we have developed a selection of texts that can help form a "bibliographic" narrative useful for verifying the starting idea of the relationship between space and food.